Host–Guest Binding Hierarchy within Redox‐ and Luminescence‐Responsive Supramolecular Self‐Assembly Based on Chalcogenide Clusters and γ‐Cyclodextrin. Issue 51 (21st August 2018) - Ivanov, Anton A.; Falaise, Clément; Abramov, Pavel A.; Shestopalov, Michael A.; Kirakci, Kaplan; Lang, Kamil; Moussawi, Mhamad A.; Sokolov, Maxim N.; Naumov, Nikolay G.; Floquet, Sébastien; Landy, David; Haouas, Mohamed; et al.
Abstract: Invited for the cover of this issue are Anton A. Ivanov, Mohamed Haouas, Stéphane Cordier, Pavel Abramov, Emmanuel Cadot, and co‐workers involved within the CLUSPOM‐CNRS International Laboratory, including the Nikolaev Institute of Inorganic Chemistry (Novosibirsk, Russia) University of Versailles Saint Quentin and University of Rennes 1 (France). The image has been designed by Mrs. Alice Gronier (UVSQ) from an original idea of Dr. Pavel Abramov (NIIC). The cover picture depicts redox and luminescent octahedral clusters [Re6 Q8 (CN)6 ] 4− that interact through supramolecular host–guest process, with biocompatible macrocycles such as γ‐cyclodextrin. Read the full text of the article at10.1002/chem.201802102 . Abstract : " Manipulation of rhenium‐containing octahedral clusters in aqueous solution revealed their high propensity to interact with γ‐cyclodextrin to give close host–guest supramolecular assemblies ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 13467 ff. (DOI:10.1002/chem.201802102 ).